Faktor-Faktor Leverage Laporan Keuangan Yang Mempengaruhi Financial Distress - Febriyani, Indah; Rifkhan, Rifkhan (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
This study aims to analyze leverage factors that affect financial distress. This research was conducted by analyzing the financial statements of companies in the Basic Materials sector listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2022. The samples used in this study were 24 Basic Materials sector companies listed on the Indonesia Stock Exchange during the period 2017 to 2022 using purposive sampling techniques. The data used in this study is secondary data in the form of financial statements from each company that has been used as a research sample. The variables used in this study are Debt to Assetss Ratio (DAR) (X1) as the first free variable, Debt to Equity Ratio (DER) (X2) as the second independent variable, and Long Term Debt to Equity Ratio (LTDER) (X3) as the third independent variable and Financial Distress (Y) as the dependent variable. The panel data regression method was used as a research methodology in this study. Analysis of research results using the help of EViews 12 Student Version Lite software. The results showed that the best model was the Random Effect Model (REM). The results of this study show that Debt to Assetss Ratio (DAR) and Debt to Equity Ratio (DER) partially affect financial distress. While the Long Term Debt to Equity Ratio (LTDER) partially has no effect on financial distress and simultaneously the Debt to Assetss Ratio (DAR), Debt to Equity Ratio (DER) and Long Term Debt to Equity Ratio (LTDER) affect financial distress.